Q: What is 6x plus 3y-2x plus 5y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It's an algebraic expression that can be simplified to: x-5y

It is: 6x-5y simplified

86

The question is not quite clear, do you mean -6x+3y = -18 and -10+5y = -30? If so then the solution is: -10+5y= -30 5y = -30+10 5y = -20 y = -4 Substitute the value of y into the equation -6x+3y = -18: Answer: x = 1 and y = -4

The given expression can be simplified to: x-5y

Related questions

(6x)(5y)

(6x - 5y) + (-3x - 4y) =6x - 5y - 3x - 4y =3x - 9y =3 (x - 3y)

x= -1 y=-1

4x-2y

It's an algebraic expression that can be simplified to: x-5y

It is: x-5y simplified

It is: 6x-5y simplified

86

The question is not quite clear, do you mean -6x+3y = -18 and -10+5y = -30? If so then the solution is: -10+5y= -30 5y = -30+10 5y = -20 y = -4 Substitute the value of y into the equation -6x+3y = -18: Answer: x = 1 and y = -4

6x and 5y

6x - 5y = 15 6x - 6x - 5y = 15 - 6x -5y = -6x + 15 (-5y)/-5 = (-6x)/-5 + 15/-5 y = 6/5x - 3 where 6/5 is the slope and y-intercept is -3.

The given expression can be simplified to: x-5y